2021
DOI: 10.1155/2021/8001787
|View full text |Cite|
|
Sign up to set email alerts
|

A Novel Curcumin-Based Drug Powder Inhalation Medicine for Chronic Obstructive Pulmonary Disease

Abstract: The dry powder inhaler is a new form of drug delivery that is widely used as an alternative to traditional drug delivery methods, addressing the shortcomings of traditional drug delivery methods and obtaining better therapeutic results. This mode of delivery is also one of the most rational ways to treat pulmonary diseases such as chronic obstructive pulmonary disease (COPD). Curcumin, a natural polyphenol, has been shown to be effective in the treatment of COPD. In this study, different concentrations of curc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…The major limiting factor of curcumin medical applications is its low bioavailability. However, there is a new treatment formulation using dry powder inhalation of curcumin for COPD that can provide good solubility and dissolution [113]. There are several classes of polyphenols present in apple juice, including flavanols, dihydrochalcones, flavan-3-ols and phenolic acids.…”
Section: Polyphenols Treatment Via Inflammasome In a Cigarette Smokin...mentioning
confidence: 99%
“…The major limiting factor of curcumin medical applications is its low bioavailability. However, there is a new treatment formulation using dry powder inhalation of curcumin for COPD that can provide good solubility and dissolution [113]. There are several classes of polyphenols present in apple juice, including flavanols, dihydrochalcones, flavan-3-ols and phenolic acids.…”
Section: Polyphenols Treatment Via Inflammasome In a Cigarette Smokin...mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%